Choking - Karwatzki, Walter (Revista do Colóquio, 2023)
In the test, the issue of asphyxiation is not just mechanical, it is caused by the lack of O2. The essay deals with the issue of suffocation that contemporary society subjects us to. The social suffocations of our daily lives.